A Comparative Study Between Virtual-Based Rehabilitation and Traditional Therapy for Improving Coordination in Traumatic Brain Injury Patients with Manual Muscle Testing Above Grade 3 - Vyas, Rinshum; Lohar, Deepak; Khan, Jafar; Balala, Deepika; Menria, Shubham; Rai, Richa Hirendra; Pal, Renuka; Gurjar, Bhavini; Kapoor, Shilpi; Vashi, Achalkumar (Journal of Neonatal Surgery, 2025)
Background: Traumatic Brain Injury (TBI) often disrupts coordination, impacting functional independence. Virtual-Based Rehabilitation (VBR) is emerging as a promising alternative to traditional therapies by enhancing patient motivation through immersive experiences. Objective: To compare the efficacy of VBR and traditional physiotherapy in improving coordination among TBI patients with Manual Muscle Testing (MMT) scores above Grade 3. Methods: A randomized controlled trial included 60 TBI patients aged 18–65 years, divided into two groups—Group A (Traditional Therapy, n=30) and Group B (VBR, n=30). Both groups received 45-minute sessions three times weekly over 6 months. Outcome measures included the Barthel Index (BI) and Berg Balance Scale (BBS). Data analysis used paired and unpaired t-tests with significance at p < 0.05. Results: Both groups showed significant improvements in BI and BBS scores (p < 0.05). Group B showed marginally better gains, though not statistically significant compared to Group A. Conclusion: Both rehabilitation methods significantly enhance coordination in TBI patients with MMT > Grade 3. VBR offers an engaging and potentially more motivating option for neurorehabilitation